PENGARUH KEMAMPUAN KOMUNIKASI KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP PRESTASI KERJA GURU SMK - Samto, Samto; Wahyudi, Wahyudi; Sukmawati, Hj. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractTeacher work performance is the level of success of a teacher in completing tasks or work entrusted by the leadership. Teacher work performance has the potential to be influenced by the principal's ability to communicate, and is influenced by good work attitudes and (cultural) behavior by teachers. Because in completing the work of an organization requires effective communication from the principal and is inseparable from the nature of cultural values such as discipline, motivation and competition that will form the norms, attitudes, habits and behavior of individuals who become the cultural identity of the organization. The ability of principals to communicate with teachers in their school organizations is one of the factors increasing teacher work performance and the culture of school organizations is a decisive factor for the success or failure of the organization in the coming decades and makes teachers wiser in their behavior and improve work performance. In order for the Sambar sub-district 1 vocational high school teachers to have good work performance, several things are needed to motivate their work performance, namely: 1) School principals give teachers broader trust and opportunities to perform their main tasks and functions professionally, build joint work commitments, and open attitude. 2) The culture of school organizations needs to be built and familiarized so that it becomes a unique identity in carrying out learning activities, especially the culture of individual or team initiatives in taking work actions, carrying out innovations and initiatives, building communication and competition patterns, and tolerance for risk and conflict. Therefore, principals and vocational teachers in sub-district 1 of Sambas Regency need to pay attention and improve aspects of communication skills and culture of school organizations, because both of them have been proven to be empirically influential on teachers' work performance. The greater the value of the communication skills of the principal and organizational culture, the greater the value of teacher work performance. Keywords: Job Performance, Communication, Organizational Culture.